(untitled) (Journal of Environmental Microbiology and Toxicology, 2020)
Thermodynamic studies on adsorption process play a vital role in the estimation of adsorptive mechanisms (both physical and chemical). Estimating the accuracy of thermodynamic parameters is dependent upon the equilibrium constants between two phases (KL: dimensionless). In this study, thermodynamic parameters were calculated from the KL constant derived from the adsorption of Langmuir isotherms of Pb(II) on an sulphuric acid-treated brown algae Cystoseira stricta biomass at different temperatures. The conversion of the KL values to the dimensionless Kc values based on the Langmuir model was then assessed for thermodynamic parameters via the Van’t Hoff’s equation. The Pb(II) adsorption process onto the Cystoseira stricta biomass was spontaneous and feasible with DG values at 25, 30, 35 and 40 oC of -24.56 (95% C.I., -24.00 to -25.03), -22.60 (95% C.I.,-21.95 to -23.12), -20.90 (95% C.I.,-18.87 to -22.01) and -17.17 (95% C.I.,-17.71 to -21.41), respectively, and occurred in an endothermic nature (DH= -0.30 kJ/mol (95% C.I., -194.34 to 193.74) with an increased in randomness (DS= -299.47 J/mol×K (95% C.I., -553.60 to -45.35) kJ/mol). To confirm the accuracy and precision of the asymptotatic 95% confidence interval, Monte Carlo simulation may be carried out in the future.